Transcriptome Sequencing Unravels Potential Biomarkers at Different Stages of Cerebral Ischemic Stroke - Cai, You; Zhang, Yufen; Ke, Xiao; Guo, Yu; Yao, Chengye; Tang, Na; Pang, Pei; Xie, Gangcai; Fang, Li; Zhang, Zhe; Li, Jincheng; Fan, Yixian; et al. (Frontiers in Genetics, 2019)
Ischemic stroke, which accounts for 87% of all strokes, constitutes the leading cause of morbidity and mortality in China. Although the genetics and epigenetics of stroke have been extensively investigated, few studies have examined their relationships at different stages of stroke. This study assessed the characteristics of transcriptome changes at different stages of ischemic stroke using a mouse model of transient middle cerebral artery occlusion (tMCAO) and bioinformatics analyses. Cerebral cortex tissues from tMCAO mice at day 1, 3, 7, 14, and 28 were removed for RNA-Seq and small RNA-Seq library construction, sequencing, and bioinformatics analysis. We identified differentially expressed (DE) genes and miRNAs and revealed an association of the up-regulated or down-regulated DEmiRNAs with the correspondingly altered DEgene targets at each time-point. In addition, different biological pathways were activated at different time-points; thus, three groups of miRNAs were verified that may represent potential clinical biomarkers corresponding to day 1, 3, and 7 after ischemic stroke. Notably, this represents the first functional association of some of these miRNAs with stroke; e.g., miR-2137, miR-874-5p, and miR-5099. Together, our findings lay the foundation for the transition from a single-point, single-drug stroke treatment approach to multiple time-point multi-drug combination therapies.